"Value Engineering" In United States Of America - Maral Papazian Bedian (Deep Foundations Institute, 2002)
Construction contracts in the USA contain the clause "Value Engineering" ? an interesting and curious clause allowing contractor initiated design changes. Misleading is the interpretation of value engineering implying cost saving and sharing with the owner, and curious is the timing, just before beginning of actual construction. It is not surprising that such a clause would simply be ignored, because it involves change, often major design changes in very short time; and change is feared, moreover, it is vehemently resisted by all parties, owner, designer, contractor. The problem in the USA may lie in the divergence and separation of the two entities: Designer/Engineer and Builder/Contractor, assigned to the "one" engineering project. The priorities and incentives of these two groups are very different. The Engineer spends years, even decades, in design and prepares contract drawings often without a deep understanding of construction methods. Worse, with all the time available to him and in our era of tremendous advances in computational methods and speed, the designer turns in plans that are inexcusably exaggerated code-based design with excessive safety factors. As to the Contractor, he builds, often without appreciation of design principles or regard for design engineers. Redesign to apply a new technology or optimization of an inferior design just before construction becomes unthinkable. It is not surprising that adverse and hostile relationship between the designer and the contractor is a norm with extended disputes and claims, not to mention the cost these entail. Surprisingly, "Value Engineering" was successfully implemented in record speed on several very large projects in the metropolitan New York area. The process of change was unconventional, painful, and even comical. Four case studies are presented: two Design/Build: the 1.2 billion dollars Hudson-Bergen Light Rail Transit System in New Jersey and the 90 million dollars MTA Bus Depot in Manhattan, and two Conventional Design/Bid/Build: the 90 million dollars Queens Boulevard Bridge and the 150 million dollars Long Island Expressway.